Workplace Violence in Tertiary Hospitals: Unraveling Its Detrimental Effects on Healthcare Workers’ Job Engagement - Balsak, Habip; Özel, Mehmet (La Medicina del Lavoro, 2025)
Background: Workplace (WPW) violence is a significant issue among healthcare workers (HCWs) in hospitals and negatively impacts the healthcare workforce. WPW can have more severe consequences, especially in tertiary hospitals with a concentrated, specialised workforce. In this regard, the study aimed to identify the dynamics of workplace violence exposure among HCWs in a tertiary hospital. It also investigated its impact on job engagement. Methods: The study was designed as a descriptive cross-sectional study conducted between June and September 2023. The study involved 3,526 HCWs at a tertiary hospital in Turkey, all invited, with 390 participating. The study examined healthcare workers' ability to handle WPV. It also examined their exposure to violence, their perception of safety against violence at work, and their engagement in their jobs. Results: Exposure to WPV among HCWs included in the study significantly predicts job engagement, with a negative relationship (β: -0.473). Additionally, as HCWs' skills in managing WPV increase, job engagement also increases (β: -0.279). Among younger and less experienced HCWs, WPV exposure and job engagement scores were significantly lower (p